Motivational Interviewing and Physical Activity on Quality of Life of Type 2 DM Patients in Makassar City - Ridwan Amiruddin; Nurhaedar Jafar; Jumriani Ansar; Uliadi Barrung Limbong; Risnah (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: This study aimed to see the effect of a combination of motivational interviewing and physicalactivity programs on the quality of life of patients with type 2 diabetes mellitus (type 2 DM).Methods: The design of this study was a quasi-experimental with a non-randomized control group pretestposttest design. The population was all patients with type 2 DM who were recorded in the medical records ofPublic Health Centers. The sampling technique was exhaustive sampling with a sample size of 30 people inthe intervention group and 30 people in the control group. Using bivariate data analysis, the two dependentmean difference test and two independent mean difference tests were used.Results: Statistical analysis show that there are differences in the mean value of the four domains ofquality of life in the intervention group before and after treatment (p = 0.0001 for each domain of PhysicalHealth, Psychological Conditions, Social Relations, and Environmental Conditions); there is a differencein the quality of life of type 2 DM patients between the intervention group and the control group with thepercentage of improving the quality of life in the good category in the intervention group after being giventreatment by 66.7% (p= 0.0001).Conclusion: Providing a combination of counseling programs with a motivational interviewing approachwhich is followed by gymnastics exercise is effective in improving the quality of life of type 2 DM patients.